PEMULIHAN EKONOMI NASIONAL MENUJU DEMOKRASI EKONOMI - Mubyarto, Mubyarto (Journal of Indonesian Economy and Business, 2001)
Since the monetary and economic crisis in mid-1997 there has never been agreement, or serious debate, on how to measure economic recovery. Is it when foreign exchange rate can be stabilized or after banking recapitalization and business restructurization can be fully implemented? Even when economic growth has resumed mid-1999 and the beginning of 2000, some economist argued that it is still an artificial growth when investment has not recovered to the pre-crisis level.The article proposes different view: that is, because of the important role the Ekonomi Rakyat (estimated about 50-60% of total Indonesian economy), the economic recovery has taken place, and the ekonomi rakyat has made adjustment to the changing situation relatively easily. The argument has been strengthened by our research findings in the regions (provinces, kabupaten, and villages) which shows much smaller rate of economic contraction in 1998. It is expected that regional autonomy to be implemented in the beginning of 2001 will speed up the process of the development of ekonomi rakyat and the realization of economic democracy in the regions and the country as a whole.Keywords: economic recovery, conglomeration, ekonomi rakyat, and regional autonomy.